The Effectiveness of Tui Na Massage to Increase the Application Of Toddlers - Shelaa Maulana Kholbi Anisya; Siti Farida (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
The problem that is often experienced by children aged 1-5 years is that it will become difficult to eat. Difficulty eating conditions is a problem in providing food as an effort to meet nutritional intake in children and toddlers. One of the causes of children having difficulty eating is digestive problems. Vomiting, spilling food and brushing off bites are symptoms of a child not having an appetite. One of the actions to overcome children who do not have an appetite is by doing Tui Na Massage. Tui Na massage is a massage technique to overcome eating difficulties in toddlers by improving blood circulation in the spleen and digestion. This type of research is a Pre-Experimental Design with One Group Pretest-Postest Design, namely by comparing 1 group with 2 treatments, namely observing the frequency of appetite for toddlers before and after being given Tui Na massage. The sample in this study were toddlers who met the inclusion criteria as many as 20 toddlers. The results of statistical tests obtained p-value of 0.000 so it can be concluded that Tui Na massage is effective for overcoming the problem of difficult eating in toddlers. The frequency of eating in toddlers increases after the Tui Na massage. Parents are expected to apply Tui Na massage once a day for 6 consecutive days on their toddlers to overcome appetite problems so that toddler growth and development can be achieved optimally.